2006
DOI: 10.1002/lsm.20376
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of calculus retropulsion on pulse duration during HO: YAG laser lithotripsy

Abstract: Less retropulsion and equivalent fragmentation occurred when Ho:YAG pulse duration increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 40 publications
2
52
1
Order By: Relevance
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…8,12,16,[20][21][22] Some of these reports have shown images of small residual effects of the bubble collapse behind the fiber tip. 12,19 This is presumably due to a collapsing bubble-induced pressure wave propagating in the axial direction of the fiber, both toward and away from the fiber tip. Although this pressure wave has been observed to be too weak to induce photomechanical ablation of urinary stones, it has been shown to be sufficiently strong to push stones away from the fiber tip.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have also used PoP stone phantoms to model urinary stones because of their comparable tensile strength. 11,12 Each stone was dried for at least 24 h and weighed using an analytical balance (AB54-S, Mettler-Toledo, Switzerland). The stones were monitored throughout the suction experiments, and any damaged stone was removed and replaced.…”
Section: Stone Suction Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous Ho:YAG laser lithotripsy retropulsion studies also have reported that the use of lower pulse energies, longer pulse durations, higher pulse rates, and smaller optical fiber diameters is the optimal combination of laser parameters for minimizing stone retropulsion. [17][18][19][20][21][22] The TFL technology is ideally suited for operation with this combination of laser parameters.…”
Section: Stone Phantom Retropulsion Studiesmentioning
confidence: 99%